External-Cavity Quantum Cascade Laser Spectroscopy for Mid-IR Transmission Measurements of Proteins in Aqueous Solution - Alcaraz, Mirta Raquel (2015)
In this work, we report mid-IR transmissionmeasurements of the protein amide I band in aqueous solution atlarge optical paths. A tunable external-cavity quantum cascade laser(EC-QCL) operated in pulsed mode at room temperature allowedone to apply a path length of up to 38 μm, which is four times largerthan that applicable with conventional FT-IR spectrometers. Tominimize temperature-induced variations caused by backgroundabsorption of the ν2-vibration of water (HOH-bending) overlappingwith the amide I region, a highly stable temperature control unitwith relative temperature stability within 0.005 °C was developed.An advanced data processing protocol was established to overcomefluctuations in the fine structure of the emission curve that areinherent to the employed EC-QCL due to its mechanical instabilities. To allow for wavenumber accuracy, a spectral calibrationmethod has been elaborated to reference the acquired IR spectra to the absolute positions of the water vapor absorption bands.Employing this setup, characteristic spectral features of five well-studied proteins exhibiting different secondary structures couldbe measured at concentrations as low as 2.5 mg mL−1. This concentration range could previously only be accessed by IRmeasurements in D2O. Mathematical evaluation of the spectral overlap and comparison of second derivative spectra confirmexcellent agreement of the QCL transmission measurements with protein spectra acquired by FT-IR spectroscopy. This provesthe potential of the applied setup to monitor secondary structure changes of proteins in aqueous solution at extended opticalpath lengths, which allow experiments in flow through configuration.